Eksistensi Kedudukan Peraturan Menteri terhadap Peraturan Daerah dalam Hierarki Peraturan Perundang-Undangan - Juwita Putri Pratama; Lita Tyesta ALW; Sekar Anggun Gading Pinilih (The Constitutional Court of the Republic of Indonesia, 2022)
Ministrial Regulations as Legislative Regulations aren’t regulated in their position. This causes hierarchy confusion in the Ministerial Regulation faced with the Regional Regulation. This study aims to determine the hierarchy of regulation of Ministerial Regulations and the legal consequences that arise between it if they are mentioned in the hierarchy. This paper’s method is normative-juridical with descriptive analysis. This paper uses library research and interviews. The data analysis method used is qualitative analysis. The result of this research is that Law Number 12 of 2011 concerning the Establishment of Legislation doesn’t regulate Ministerial Regulations either being part of the hierarchy or from outside the hierarchy. Even so, viewed from the concept of a unitary state, ministerial regulations are part of the central level legislation. When the Ministerial Regulation is put up against the Regional Regulation, this has a number of legal effects.